Developing A Padlet Integrated E-Module for Teaching Descriptive Writing - Kanna Ardanisa; Aseptiana Parmawati; Ningtyas Orilina Argawati (PROJECT (Professional Journal of English Education), 2026)
This study aimed to develop and validate a padlet-assisted e-module for teaching descriptive writing to seventh grade junior high school students and to investigate students’ responses toward the developed product. The study employed the Research and Development (R&D) method adapted from Borg and Gall and modified by Sugiyono. The procedures consisted of needs analysis and product development, expert validation, limited trial, wider trial, and dissemination. The participants were seventh grade students at a junior high school in Cimahi. Data were collected through observation sheets, validation sheets, and student response questionnaires. The findings revealed that the developed e-module was categorized as highly feasible based on expert validation results, with an average score of 86.36%, particularly in terms of visual design, readability, interactivity, and material suitability. Students also showed positive responses during the wider trial, with an average response score of 85.09%, categorized as very good. The integration of Padlet facilitated collaborative learning activities through publishing, commenting, peer feedback, and interaction during writing activities. In addition, visual prompts and guided writing exercises helped students generate ideas and organize descriptive texts more systematically. The novelty of this study lies in integrating Padlet directly into a systematically designed e-module that combines instructional materials, collaborative learning activities, visual prompts, and guided writing tasks within a single digital platform for descriptive writing instruction.